DEVELOPMENT OF THE STORY OF SCHOOL EDUCATIONAL GAME TO ENHANCE CAREER EXPLORATION AMONG JUNIOR HIGH SCHOOL STUDENTS IN MALINAU KOTA DISTRICT - Lulus Eka Utama; Aprilia Tina Lidyasari (SOSIOEDUKASI, 2026)
Career exploration is an essential developmental task for junior high school students because it helps them understand their personal potential, educational opportunities, and future career pathways. However, many students experience difficulties in obtaining adequate career information due to limited guidance services, insufficient learning resources, and the lack of innovative career guidance media. This study aimed to develop the Story of School educational game as a career guidance medium, determine its feasibility and practicality, and evaluate its effectiveness in improving students’ career exploration. The study employed a Research and Development (R&D) approach adapted from the Borg and Gall development model. The participants consisted of 56 eighth-grade students from SMP Negeri 1 Malinau Kota and SMP Negeri 3 Malinau Kota. Data were collected through expert validation questionnaires, student response questionnaires, and a career exploration scale. The data were analyzed using descriptive quantitative techniques, the Wilcoxon Signed-Rank Test, and N-Gain analysis. The findings revealed that the Story of School game was successfully developed using RPG Maker MV as an educational game-based career guidance medium. The product was categorized as highly feasible, obtaining validation scores of 94.64% from material experts, 96.88% from media experts, and 93.75% from guidance and counseling practitioners. The practicality assessment showed a very positive student response with an average score of 98.78%. Furthermore, the effectiveness test indicated a significant improvement in students’ career exploration, evidenced by the Wilcoxon Signed-Rank Test result (p = 0.000 < 0.05) and an N-Gain score of 0.5811, which falls within the moderate category. These findings suggest that the Story of School educational game is a feasible, practical, and effective medium for supporting career guidance services and enhancing career exploration among junior high school students.